2014
DOI: 10.2478/s13536-013-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimization of NiFe2O4 nanoparticles synthesized by mechanical alloying

Abstract: In this study, the Taguchi robust design method is used for optimizing ball milling parameters including milling time, rotation speed and ball to powder weight ratio in the planetary ball milling of nanostructured nickel ferrite powder. In fact, the current work deals with NiFe 2 O 4 nanoparticles mechanochemically synthesized from NiO and Fe 2 O 3 powders. The Taguchi robust design technique of system optimization with the L9 orthogonal array is performed to verify the best experimental levels and contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…NiFe 2 O 4 ferrite with a completely inverse structure is an important member in the spinel structural family [4]. In recent years, due to their specific physical and chemical properties, the synthesis of 1D and 2D magnetic nickel ferrite nanomaterials is becoming a hot topic in this area.…”
Section: Introductionmentioning
confidence: 99%
“…NiFe 2 O 4 ferrite with a completely inverse structure is an important member in the spinel structural family [4]. In recent years, due to their specific physical and chemical properties, the synthesis of 1D and 2D magnetic nickel ferrite nanomaterials is becoming a hot topic in this area.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing milling time up to 18 h, a spontaneous combustion reaction initiated between the NiO and Fe 2 O 3 powder particles to produce Ni-ferrite. It is worth mentioning that the details of phase formation, structural changes of the milled powders of the Ni-ferrite have been reported in our previous published papers [14,15]. Here, we are going to explain a formation of Ni-ferrite by self-propagating high temperature (SHS) through the thermodynamic data.…”
Section: Resultsmentioning
confidence: 93%
“…The formation of Ni-ferrite, in this study, during the milling process, an aspect not covered by the Yang et al investigation, can be associated with the milling conditions such as type of mill, rotation speed, ballto-powder mass ratio, milling time, and grinding media. The effects of these variable parameters on the Ni-ferrite system in details have been reported in our previous published work [14]. Therefore, in this study, it was attempted to investigate a probable type of reaction mode during the milling process, thermal stability and to evaluate the changes which occurred during the milling process by means of differential scanning calorimetry (DSC).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that impurity free CdFe2O4 nanoparticles were obtained at 800 0 C. The diffraction peaks observed at 2θ = 28.725, 33.85, 41.182, 45.06, 51.089, 54.474, 59.806, 67.832 and 70.697 0 indicated the planes of (220), (311), (400),(331), (422), (511), (440), (620) and (533) respectively. X-ray density ( X) was calculated using the relation [26]:…”
Section: Figure 1 Xrd Pattern Of Cdfe2o4mentioning
confidence: 99%